Antimicrobial, synergistic and autophagic effects of medicines for Malaria venture pathogen box compounds on resistant strains of Mycobacterium tuberculosis and Neisseria gonorrhoeae - Fourie, Petrus Bernardus (University of Pretoria, 2023)
Thesis (Medical Microbiology)--Univeristy of Pretoria, 2023.